A comparison study on energy savings and fungus growth control using heat recovery devices in a modern tropical operating theatre - Yau, Yat Huang; Ng, W.K. (Elsevier, 2011)
Fungus growth has always been a problem in hot and humid areas. This particular problem is crucial for operating theatre as it could affect the success rate of operations. Many postoperative fungus infection cases had occurred in the past, and it is generally agreed that air-conditioning system play a very important role in resolving the fungus growth problem. Besides air quality, the energy consumption level of air-conditioning system is also very important. In this study, the operating theatre 3 in Putrajaya Hospital, Malaysia was chosen as the research subject. The air-conditioning system for OT3 was redesigned with the energy recovery wheel, desiccant dehumidifier and heat pipe heat exchanger to achieve the objectives of this study. A computer program called Transient system simulation program (TRNSYS) was utilized for analysis in this research. From the outcome of simulations, it was found that the heat pipe heat exchanger could reduce the most energy consumed by the air-conditioning system. It managed to reduce the energy consumption by 57.85%. Moreover, the payback period of the device is only 0.95 years, which is the shortest among all the systems studied. Therefore, applying heat pipe heat exchanger is a good choice to save energy and resolve fungus growth problem in hot and humid areas. © 2010 Elsevier Ltd. All rights reserved.